Outcomes and risk factors of very low birth weight infants with intraventricular haemorrhage who received respiratory support in a middle income country neonatal unit - Goolab, Deepika (Department of Paediatrics and Child Health, 2021)
Background: Prematurity is a major risk factor for intraventricular haemorrhage (IVH). Premature infants often require respiratory support. There is little information on neonates with IVH who require respiratory support in low and middle income countries. Objective: To describe the characteristics and short-term outcomes of very low birth weight (VLBW) infants with IVH who required respiratory support in a tertiary neonatal unit with resource limitations. Methods: This was a matched retrospective observational study. The population included VLBW infants with IVH, who received positive pressure respiratory support between January 2014 and December 2016. Outcomes of infants with severe IVH was compared to those with mild IVH. Outcomes were further analysed according to mode of ventilation. Results: 150 infants were included in the study, 56 (37%) received continuous positive airway pressure (CPAP) only and 94 (63%) mechanical ventilation. Severe IVH was associated with surfactant therapy across both ventilation groups (p=0.03). Oxygen requirement at 28 days was more frequent in infants with severe IVH compared to mild IVH (79% vs 38%, p=0.01) (OR 6.11 (95% CI 1.19-31.34), p=0.03). Severe IVH and the presence of coagulopathy were the strongest predictors of death in both ventilation groups (p <0.0001). Pulmonary haemorrhage was the commonest cause of death in those with severe IVH and blood culture confirmed sepsis in those with mild IVH. Periventricular leukomalacia (PVL) was associated with severe IVH in those receiving invasive ventilation (OR 6.67 (95% CI 1.11-40.17)). Conclusion: Mechanical ventilation, coagulopathy and pulmonary haemorrhage were strongly associated with death in VLBW infants with severe IVH in a resource-limited setting. These prognostic factors may have a role in end of life decisions.